ANALYSIS OF THE APPLICATION OF BALANCED SCORECARD TO THE PERFORMANCE OF MICRO SMALL MEDIUM ENTERPRISES ENGGAL FURNITURE INDUSTRY - Junisa Anugra Putri, Ikbal Mahadi Aziz; Ummul Khair (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
The performance of medium-sized MSMEs is a description of the performance conditions of an MSME which is analyzed by four perspectives of Finance, Customers, Internal Business, Learning and Growth, This study aims to determine the performance of Enggal Furniture using the balance scorecard method.This research was conducted at Enggal Furniture. The type of data used in this study is qualitative data while the data sources are primary, secondary. Data collection methods are carried out using documentation, interviews. Data analysis techniques using balance scorecard analysis with four perspectives, namely: financial perspective, customer perspective, internal business process perspective, and growth and learning.The results of the financial perspective research net profit margin performance level is quite good gross profit margin performance level is very good and good. Customer perspective, customer retention performance level is quite good and good while customer acquisition performance level is quite good. Internal business process perspective, Innovation performance level is not good, AETR is at a bad performance level. While the growth and learning perspective for employee performance levels is included in the performance level is not good.